Estimating the value of the World Heritage Site designation: a case study from Sagarmatha (Mount Everest) National Park, Nepal. Issue 12 (2nd December 2017) - Baral, Nabin; Kaul, Sapna; Heinen, Joel T.; Ale, Som B.
ABSTRACT: This paper estimates the economic value of World Heritage Site (WHS) designation for the Sagarmatha (Mount Everest) National Park, Nepal. In 2012, entrance fees were 30 per international visitor; lower fees apply to South Asian visitors, and no fees to domestic visitors. We surveyed 522 international visitors to the Park in 2011 to elicit their willingness to pay (WTP) for access, using the contingent valuation method. Logistic regression results show that bid amounts, gender, age, educational attainment, use of a guide, length of stay in the park, information about park substitutes, and knowledge about the park's WHS designation predicted visitors' WTP decisions. The median WTP amount was US90.93 per trip; 63.8% of visitors were willing to pay more than the existing entry fee. The revenue maximizing entry fee was 80 per trip. Knowledge about the park's WHS designation prior to their trip contributed 16.39 to the median WTP: better marketing of the site's WHS status could add up to US 566, 619 to the site's annual income. Given that many protected areas now suffer falling public sector financial help, accurate knowledge of WTP is increasingly key to supporting sustainable management in WHS sites, and in justifying tourism to them.